Faktor-Faktor UMEGA yang Mempengaruhi Penerimaan Pengguna terhadap Layanan SIBERAS di Desa Bulo - Bayu Irghiaksa; Herman Dema; Sandi Lubis (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines the challenges in implementing e-government services in Bulo Village, which uses the SIBERAS application to improve accessibility and transparency of public services. Although this application is designed to facilitate community access to services, there are various obstacles to its acceptance and utilization. The main objective of this study is to analyze the factors that influence the acceptance of SIBERAS services using the UMEGA model. The approach used in this research is quantitative, with data collection through questionnaires distributed to 112 active users of SIBERAS. The data collected was then analyzed using SPSS software. The results showed that performance expectations, effort expectations, and social influence have a significant positive relationship with user attitudes toward SIBERAS services. In addition, facilitating conditions and user attitudes affect the intention to continue using this service. This study indicates that technology acceptance in rural areas is influenced more by perceived benefits and ease of use than by risk or infrastructure readiness concerns. Therefore, practical factors such as ease of access and direct benefits from using the application have a greater influence in driving technology adoption than other risk or facility readiness issues